2019
DOI: 10.1111/apa.15047
|View full text |Cite
|
Sign up to set email alerts
|

Children report positive experiences of animal‐assisted therapy in paediatric hospital care

Abstract: Aim To evaluate children's experiences of and responses to animal‐assisted therapy using a therapy dog as complementary treatment in paediatric hospital care. Methods The study was performed using mixed methods, by means of qualitative and quantitative data. Fifty children in a paediatric surgery ward, at a tertiary hospital in Sweden, were included between February 2016 to May 2017. Children answered questions about feelings of well‐being and experiences of the hospital stay before and after animal‐assisted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
(47 reference statements)
3
16
0
2
Order By: Relevance
“…It seems likely that faster rapport and better connections with patients, as catalysed by the facility dog, would augment success in the role of a child‐life specialist. This is consistent with findings that, after visiting with a therapy dog, paediatric patients described healthcare professionals as friendly and as making their hospital stays easier (Lindström Nilsson et al, 2020). On the other hand, there was no significant relationship between working with a facility dog and burnout in terms of perceived emotional exhaustion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It seems likely that faster rapport and better connections with patients, as catalysed by the facility dog, would augment success in the role of a child‐life specialist. This is consistent with findings that, after visiting with a therapy dog, paediatric patients described healthcare professionals as friendly and as making their hospital stays easier (Lindström Nilsson et al, 2020). On the other hand, there was no significant relationship between working with a facility dog and burnout in terms of perceived emotional exhaustion.…”
Section: Discussionsupporting
confidence: 90%
“…According to prior research, therapy dogs may provide significant benefits to paediatric patients’ physical and mental health, including reduced fear, anxiety and perceived pain (e.g. Crossman et al, 2020; Lindström Nilsson et al, 2020). Some hospitals feature full‐time therapy dogs, termed ‘facility dogs’, that work with paediatric healthcare professionals in goal‐directed practices to improve the patient experience (Schilp, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…If the children were sad, the pets could help them feel happy again. The importance of a pet has also been confirmed in previous research [ 37 , 38 ] and stresses the therapeutic effects of having animals in care situations [ 39 ].…”
Section: Discussionmentioning
confidence: 61%
“…It seems appropriate, especially for older clients, to explain everything thoroughly and patiently and to respect possible concerns. In a study by Lindström Nilsson et al [ 43 ] on children, pediatric clients reported mixed feelings (positive and negative) before therapy and rated therapy as an unexpected event, while after AAI they all reported a positive experience. A patient approach, sufficient explanation, and time seem to help overcome any initial concerns.…”
Section: Discussionmentioning
confidence: 99%